Investigating the Factors that Hinder School-Based Vision Screening Programs at Egor Local Government Area, Benin City, Nigeria. - Femi, Daniel Ayodele (Optometry & Visual Performance, 2026)
Background: Many children worldwide experience vision impairment, much of which is preventable with early intervention. School-based vision screening programs are vital for early detection and improved academic performance. However, in countries like Nigeria, these programs often face challenges, such as poor awareness, limited resources, and low stakeholder involvement. This study aimed to evaluate the prevalence, barriers, and benefits of school-based vision screening programs in Egor LGA, focusing on identifying actionable strategies for improvement. Methods: A 14-question survey was conducted among 291 respondents, including students, teachers, administrators, and parents. The questionnaire assessed the frequency of vision screenings, barriers to implementation, perceived benefits, and recommendations for enhancing program participation. Results: Most respondents (79.7%) reported that no vision screenings had been conducted in their schools over the past year. The frequency varied among the schools conducting screenings, with only 1.7% performing screenings more than twice annually. Key barriers included a lack of awareness (33.7%), a lack of resources (23.7%), and a perceived lack of need (19.9%). Despite these challenges, respondents highlighted significant benefits, such as early detection of vision problems (49.5%) and improved academic performance (22.0%). Recommended strategies for improvement included increasing awareness campaigns (35.1%) and providing additional resources (25.1%). Conclusion: The findings reveal critical gaps in the prevalence and consistency of school-based vision screening programs. Addressing barriers through targeted awareness, resource allocation, and stakeholder engagement can significantly enhance their implementation, leading to improved vision health and student educational outcomes.